Inside Back Cover: Nanostructures and thin films of transparent conductive oxides studied by perturbed angular correlations (Phys. Status Solidi B 4/2013). Issue 4 (18th April 2013) - Barbosa, M. B.; Gonçalves, J. N.; Redondo‐Cubero, A.; Miranda, S. M. C.; Simon, R.; Kessler, P.; Brandt, M.; Henneberger, F.; Nogales, E.; Méndez, B.; Johnston, K.; Alves, E.; et al.
Abstract : Applications of nanomaterials rely on their tunable properties with large‐scale integration feasibility. Advantages can be envisaged by merging nanostructures with thin film technologies, where ion implantation can be used as an integrated part of the processes. Still, ion implantation carries along with its benefits undesired intrinsic defects. Two examples of studies were performed by Barbosa et al. (pp. 801–808 ) with the nanoscopic perturbed angular correlations (PAC) technique that probes the charge density distribution in the surroundings of chosen radioactive nuclei, thus allowing characterizing the probe's real environment at the atomic scale. The chosen studies were ZnO and Cd x Zn1− x O thin films – aimed to cover luminescence wavelengths from UV to yellow ‐ with implanted 111m Cd/ 111 Cd probe, and the technologically relevant high k‐factor Ga2 O3 nanostructures and Ga2 O3 pellets, where Cd is a potential p‐type dopant. For each case, the Cd lattice site occupancies and how and to which extent the local environment of the implanted Cd is reconstructed are studied as a function of annealing temperature.